2003
DOI: 10.1373/49.4.611
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Immunoassays for Measurement of High-Sensitivity C-reactive Protein. Phase I: Evaluation of Secondary Reference Materials

Abstract: Background: Inflammation contributes to the development and progression of atherosclerosis, and C-reactive protein (CRP) can be used as a marker to assess risk for cardiovascular diseases. As variability among existing high-sensitivity CRP (hsCRP) assays can lead to misclassification of patients and hamper implementation of population-based medical decision points, standardization of hsCRP assays is needed. Methods: We evaluated five proposed secondary reference materials, including two diluted preparations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 21 publications
1
37
0
3
Order By: Relevance
“…To overcome this problem, it is practical to incorporate common reference material and to standardize the measurement conditions as much as possible. Kimberly et al reported that unification of the reference alone does not solve variation among analytical laboratories, and varying measurement values are unavoidable due to measurement conditions, such as antibodies, measurement principles, and analytical instruments 6,8) . The gold standard of references for protein measurement is purified protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome this problem, it is practical to incorporate common reference material and to standardize the measurement conditions as much as possible. Kimberly et al reported that unification of the reference alone does not solve variation among analytical laboratories, and varying measurement values are unavoidable due to measurement conditions, such as antibodies, measurement principles, and analytical instruments 6,8) . The gold standard of references for protein measurement is purified protein.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of purified protein is generally technically easy, but no definitive or reference method is available for hs-CRP to assign reference values for the gold standard, primary and secondary materials, or measure the serum component 6) . Thus, we considered that it is most appropriate to adopt a method in which multiple analytical laboratories measure hs-CRP using reliable measurement systems that satisfy the basic performance criteria, taking the gold standard or primary reference material as the common standard, and the mean of the measured values as the consensus value 6,8,21,22) . We established the consensus value as the target from outlier-processed measured values of the initial test analyzed by the 9 laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Creatinine kinase (CK) was determined according to the method described by [28]. C-reactive protein (CRP) was determined according to [29].…”
Section: Ii5 Biochemical Analysismentioning
confidence: 99%